2017
DOI: 10.3390/nu9121362
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Fruit and Vegetable Consumption and the Oral Health-Related Quality of Life among Japanese Elderly: A Cross-Sectional Study from the Kyoto-Kameoka Study

Abstract: Objective: Many previous studies have reported that fruit and vegetable consumption is associated with a reduced risk of various disease, but whether or not their consumption is associated with the oral health-related quality of life (OHRQoL) is unclear. The objective of this study was to examine the association between the frequency of fruit and vegetable consumption and the OHRQoL in elderly subjects by sex. Methods: We analyzed cross-sectional data from a population-based Kyoto-Kameoka Study in 2012 of 3112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 49 publications
2
30
0
Order By: Relevance
“…It should be highlighted, however, that smoking is a significant risk factor in the progression of periodontitis, irrespective of the actual intake of F&V. 37 Our findings were similar to those presented by Nanri et al and Moynihan, where higher F&V consumption was also associated with better oral health-related quality of life. 38,39 Moreover, our systematic literature review indicated that incorporating F&V (especially citrus fruit and berries) into the diet, as well as nutritional education activities that stress the need for adequate intake of F&V by individuals with various forms of periodontal diseases, could lead to a significant enhancement in the oral health status by improving gingival inflammation indices 34 and inhibiting the progression of periodontitis. 22,33,34 An interesting alternative seems to be provided by the potential use of freeze-dried F&V in the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 97%
“…It should be highlighted, however, that smoking is a significant risk factor in the progression of periodontitis, irrespective of the actual intake of F&V. 37 Our findings were similar to those presented by Nanri et al and Moynihan, where higher F&V consumption was also associated with better oral health-related quality of life. 38,39 Moreover, our systematic literature review indicated that incorporating F&V (especially citrus fruit and berries) into the diet, as well as nutritional education activities that stress the need for adequate intake of F&V by individuals with various forms of periodontal diseases, could lead to a significant enhancement in the oral health status by improving gingival inflammation indices 34 and inhibiting the progression of periodontitis. 22,33,34 An interesting alternative seems to be provided by the potential use of freeze-dried F&V in the treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 97%
“…Dietary sodium, potassium, and saturated fatty acid intake estimated using this FFQ are related to all-cause mortality and cardiovascular death [23,24]. In addition, in the Kyoto-Kameoka study using this FFQ, we reported that frequency of consumption of some foods (i.e., fruit and vegetable or protein-rich foods [seafood and dairy products]) is associated with geriatric disorders such as oral health-related quality of life [25] and frailty [26]. Although we reported an association between the frequency of consumption of specific foods and geriatric disorders, the precision of ranking elderly individuals according to dietary intake using this FFQ has not been validated [21].…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies have shown a strong correlation between the intake of fruits and vegetables and other antioxidant nutrients, with oral health-related quality of life in adults [39,40,41,42]. These effects have been mainly attributed to their function in reducing oxidative stress and inflammation, and were related to intake of β-carotene, vitamin C, a-tocopherol, and omega-3-fatty acids [33,43,44].…”
Section: Introductionmentioning
confidence: 99%